Exploring attractiveness bias in workplace. - Syahirah Abdul Latiff. (2012)
The ongoing issue of attractiveness bias is known to exist in a variety of situations. This issue deserves more attention as studies have proven that it occurs subconsciously. The focal point of this paper is on attractiveness bias that occurs in the workplace, namely during hiring and promotion decisions. This paper explores how evident such bias is in the workplace, the different views by past studies that addressed the advantages and disadvantages of being attractive and also, the interaction between the different genders with attractiveness. Some studies suggested that being attractive was overall a benefit for both men and women in the workplace as they were preferred over unattractive individuals. However, other studies mentioned that gender bias also existed with attractiveness bias. This was because of the perceived enhanced sex-traits that were associated with attractive people. This association had led to discrimination against attractive women in pursuing management jobs, as the jobs were perceived to require masculine traits. Thus, the gender bias suggested that attractive men are generally at an advantage, regardless of the type of jobs. However, with the review of several studies, this paper concludes that all these depended on the nature and characteristics of the managerial job itself. Lastly, this paper recommends briefly a few ways to overcome attractiveness bias in the workplace as it implies that this is a pervasive issue that should be address to ensure fair employment practices.